2020
DOI: 10.3390/ijms21144995
|View full text |Cite
|
Sign up to set email alerts
|

From Cell Entry to Engraftment of Exogenous Mitochondria

Abstract: Mitochondrial transfer has been recognized to play a role in a variety of processes, ranging from fertilization to cancer and neurodegenerative diseases as well as mammalian horizontal gene transfer. It is achieved through either exogeneous or intercellular mitochondrial transfer. From the viewpoint of evolution, exogeneous mitochondrial transfer is quite akin to the initial process of symbiosis between α-protobacterium and archaea, although the progeny have developed more sophisticated machinery to engulf env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…Macropinocytosis is a type of pinocytosis in endocytosis that is actin dependent and forms large vacuoles; macropinocytosis is considered a pervasive and widely conserved process and may have participated in the first mitochondrial endosymbiosis event [126]. Macropinocytosis seems widely accepted since other studies have also demonstrated that MSCs and hepatocytes engulf isolated mitochondria mainly through macropinocytosis [85,127].…”
Section: Triggers Signals Of Intercellular Mitochondrial Transfer (Fi...mentioning
confidence: 99%
“…Macropinocytosis is a type of pinocytosis in endocytosis that is actin dependent and forms large vacuoles; macropinocytosis is considered a pervasive and widely conserved process and may have participated in the first mitochondrial endosymbiosis event [126]. Macropinocytosis seems widely accepted since other studies have also demonstrated that MSCs and hepatocytes engulf isolated mitochondria mainly through macropinocytosis [85,127].…”
Section: Triggers Signals Of Intercellular Mitochondrial Transfer (Fi...mentioning
confidence: 99%
“…Since mammalian horizontal transfer of mitochondria through a tunneling nanotube was reported in an in vitro experiment 20 , mitochondrial transfer has been demonstrated with various mechanisms, such as nanotubes 21 , extracellular vesicles 22 , and macropinocytosis 23 , as well as by using an artificial device 24 and a compound 25 . Although the efficiency of mitochondrial transfer did not dominate over the pre-existing mtDNA but provided additive functionality in the host cells, mechanistic insights into mitochondrial transfer with respect to cell entry and endosomal escape have been deepened 26 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it will trigger ischemic cascade reactions, including the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) opening, caspase 3 initiation, and the cytochrome c secretion, so that the apoptotic execution occurs. In the latest research, it is found that mitochondrial crosstalk between cells exerts a crucial effect on the stroke management [ 5 , 6 ]. In addition, extracellular mitochondria can be transferred to damaged neurons for aggravating or reducing the damage of neurons [ 7 ].…”
Section: Introductionmentioning
confidence: 99%